2019
DOI: 10.1108/ijphm-05-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing a long-term relationship between healthcare providers and patients – perspectives of patients at a public regional hospital, Ghana

Abstract: Purpose The purpose of this paper is to determine the factors that influence patients’ long-term relationship with healthcare providers in healthcare delivery at hospitals. Design/methodology/approach Data were gathered using 170 patients in a cross-sectional survey with quantitative research methods at a public regional hospital. Results were obtained using descriptive analysis and regression analysis. Findings Generally, the study found that the health-related factors (the reception of staff, providers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 63 publications
(117 reference statements)
1
15
0
Order By: Relevance
“…The explosion of illegal products in social media platform rises because of consumers’ ignorance to ensure the quality and safety of cosmetics products before making any purchase, which calls for further studies to understand consumers’ GPB. Although, there is a significant body of literature that focused on understanding consumer behavior in the pharmaceutical industry (Adomah-Afari et al , 2019; Rawwas et al , 2019; Stadtelmann et al , 2019; Umar, 2019), less attention has been paid to understand consumers’ purchase behavior in nutricosmetics purchase context. Therefore, the present study attempts to investigate the GPB among Malaysian consumers from the perspective of cosmetics purchases with the moderating effect of eWOM on the personal norm and GPB link.…”
Section: Cosmetics Industry As the Research Contextmentioning
confidence: 99%
“…The explosion of illegal products in social media platform rises because of consumers’ ignorance to ensure the quality and safety of cosmetics products before making any purchase, which calls for further studies to understand consumers’ GPB. Although, there is a significant body of literature that focused on understanding consumer behavior in the pharmaceutical industry (Adomah-Afari et al , 2019; Rawwas et al , 2019; Stadtelmann et al , 2019; Umar, 2019), less attention has been paid to understand consumers’ purchase behavior in nutricosmetics purchase context. Therefore, the present study attempts to investigate the GPB among Malaysian consumers from the perspective of cosmetics purchases with the moderating effect of eWOM on the personal norm and GPB link.…”
Section: Cosmetics Industry As the Research Contextmentioning
confidence: 99%
“…One study (n = 170) investigated the factors that influence patients' long-term relationships with health care providers at a public regional hospital (Adomah-Afari et al, 2019). This study concluded that health-related factors (their reception by staff, providers' attitudes, waiting time, competence and expertise, and the hospital environment) were statistically significant (Adomah-Afari et al, 2019). The primary factor in patients' decision making is recommendation by the family physician, and e-marketing is important as the internet is the major source of information among younger respondents (Bhangale, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, patients co-create value of health care services, but lack knowledge to assess medical personnel' skills and competencies (Amin & Nasharuddin, 2013;Satsanguan et al, 2015;Adomah-Afari et al, 2019). Due to information asymmetry between health care providers and patients, trust is regarded as a key aspect of provideruser relationship (Barile et al, 2014).…”
Section: The Specificity Of Health Care Servicesmentioning
confidence: 99%
“…Patient commitment to a health care provider and patient loyalty are regarded as close, however, different constructs (Moreira & Silva, 2015). Patient satisfaction is regarded as a key prerequisite for the continuance of cooperation between a patient and a health care provider (Adomah-Afari et al, 2019). In addition to satisfaction, trust has also been shown to lead to patient commitment to a health care provider (Berry et al, 2008).…”
Section: Patient Commitment To a Health Care Providermentioning
confidence: 99%